Evaluation of a blocking ELISA using a urease conjugate for the detection of antibodies to pseudorabies virus - Echeverría, María Gabriela (2000)
A blocking enzyme-linked immunosorbent assay (ELISA) using a urease conjugate (U-B-ELISA) was evaluated for screening sera for antibodies to pseudorabies virus under field conditions, A total of 764 serum samples were analyzed by U-B-ELISA. Of these, 264 were evaluated by both virus neutralization and U-B-ELISA, and the results were compared. U-B-ELISA showed 98.5% and 98.9% sensitivity and specificity, respectively. This test combines the sensitivity and specificity of the blocking ELISA format while allowing visual assessment of results.